IMPORTANCE AND IMPACT OF THE POULTRY RED MITE (DERMANYSSUS GALLINAE) IN LAYER FARMS - ANALYSIS OF FARMERS’ PERCEPTION - Miroslav Kjosevski; Danijela Horvatek Tomić; Aleksandar Dodovski (Sciendo, 2021)
Poultry red mite (PRM), Dermanyssus gallinae, causes egg drop production, anemia and can be a vector in transmitting diseases. The PRM control mainly focuses on usage of the conventional chemical biocides. The objective of this study was to analyze the farmers’ perception regarding the impact, management and control of PRM in Macedonian layer farms. The data were collected with direct on-site visits using a unified questionnaire. In total, 29 poultry farms (28% of farms in the country), all with conventional cages, were part of this study. The data were analyzed by descriptive statistics, inferential statistics and Naïve Bayes Classifier technique. In 30% of the poultry farms the farmers had observed that the flock was infested with PRM. In total, 32 different treatments against PRM were reported from the farmers, and three of them were non-biocide treatments. The most used biocides (17% of the farms) were crude oil, Formalin, Neopitroid® and disinfectants. The highest agreement regarding biocides application among the farms (38%) was before the production starts. Most of the farmers applied biocides routinely, before the infestation is evident (75%). The median costs for PRM treatment were 175€ per flock, higher in the infested farms 493±677€ compared to non - infested 100±71€, p<0.05. None of the Macedonian farmers included in the study was using monitoring method for PRM infestation, contributing to poor data records. This study highlights the need of developing unified strategy for PRM control included in the Integrated Pest Management in poultry layer farms.
Keywords: poultry red mite, Dermanyssus gallinae, laying hens, biocides, Naïve Bayes Classifier